Evaluating Progestogens for Preventing Preterm Birth International Collaborative (EPPPIC): Meta-analysis of Individual Participant Data From Randomised Controlled Trials. Issue 8 (August 2021) - Mol, B. W.; Wood, S.; Rode, L.; Tabor, A.; Aboulghar, M. M.; Porcher, R.; Senat, M.-V.; Bagga, R.; Rajaram, S.; Azargoon, A.; Bahrami, E.; Nassar, A.; et al.
Abstract : (Abstracted from Lancet 2021;397:1183–1194) Preterm birth is the most common cause of neonatal morbidity and mortality. When infants are born preterm, they are at increased risk for having difficulties at birth, health problems throughout infancy, and death during the first year of life.